2015
DOI: 10.1021/acs.jpcc.5b07828
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ligands on Charge Generation and Recombination in Hybrid Polymer/Quantum Dot Solar Cells

Abstract: Control of quantum dot surface chemistry offers a direct approach to tune the molecular interface between donor and acceptor constituents in hybrid bulk heterojunction photovoltaics incorporating organic semiconductors and colloidal quantum dots. We investigate the effects of altering the quantum dot surface chemistry via ligand exchange in blends of PbS quantum dots with the conjugated polymer poly­((4,8-bis­(octyloxy)­benzo­(1,2-b:4,5-b′)­dithiophene-2,6-diyl)­(2-((dodecyloxy)­carbonyl)­thieno­(3,4-b)­thio­p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 45 publications
2
42
0
Order By: Relevance
“…As mentioned previously, the high responsivity regime of PbS QD solid photoconductors is simultaneously accompanied by a slow operation speed of photoconductors due to the term under very low incident optical powers. From our estimate, the expected response time is ~1–3 ms, which is consistent with reported values under low optical excitation densities [ 23 , 46 ]. On the contrary, when increasing the incident optical power, one would expect a decrease in the photodevice response time, by increasing the carrier-generation level.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As mentioned previously, the high responsivity regime of PbS QD solid photoconductors is simultaneously accompanied by a slow operation speed of photoconductors due to the term under very low incident optical powers. From our estimate, the expected response time is ~1–3 ms, which is consistent with reported values under low optical excitation densities [ 23 , 46 ]. On the contrary, when increasing the incident optical power, one would expect a decrease in the photodevice response time, by increasing the carrier-generation level.…”
Section: Resultssupporting
confidence: 91%
“…Also, the ligand-exchange procedure is relevant for charge-carrier dynamics in the QD solids, since surface defects in QDs can also be generated due to an incomplete ligand substitution or charge imbalance between the ligand and the surface states [ 16 ]. These surface defects in QDs are dependent on the length and the chemical structure of the capping ligands surrounding and interconnecting the QDs [ 23 ]. Furthermore, they introduce trapping states energetically located within the QD band gap that modify the photoconductivity kinetics [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Capping, surface modication and substitution of ZnO for various applications have been studied extensively in the literature. 1,[12][13][14][15][16][17][18][19] Thus, a simple route to improve the carrier concentration of n-type semiconductors such as ZnO and to enhance the efficiency of heterojunction and photovoltaic devices has become inevitable. Surface modication of ZnO nanoparticles (NPs) by n-propylamine and thiols inuences the electronic memory effect of ZnO-polystyrene diodes.…”
Section: Introductionmentioning
confidence: 99%
“…They discovered that charge carrier transport in QDs was governed by a diffusion-controlled trapassisted recombination process. Colbert et al 37 observed charge carrier generation and recombination effects in hybrid polymer/QD solar cells through QD surface chemistry control.…”
Section: Introductionmentioning
confidence: 99%